Penurunan Tingkat Depresi pada Lansia dengan Pendekatan Bimbingan Spiritual - Syaifuddin Kurnianto; Purwaningsih Purwaningsih; Hanik Endang Nihayati (Jurnal Ners, 2011)
Introduction: Depression is mental disorder which comes from complicated stress, it can happen for everyone including the elderly. This problem is frequently not considered as the main point of view to think because it is regarded to get good condition by its way without having serious treatment. On the reality, depression which doesn't get serious treatment to solve well, it can danger the life of the elderly. The purpose of this study was to prove the in fl uence of result in the spiritual guidance in accordance with Islamic religion for the changing score (rank) depression of the elderly who lived in the region of RT 04 Kedung Tarukan Wetan Surabaya.Method: Design used in this study was pre experimental design. Population for this study were all of the elderly who lived in the region of RT 04 Kedung Tarukan Wetan Surabaya. Total sample were 10 respondents, taken according to inclusion criteria. The independent variable was the spiritual guidance in accordance with Islamic religion where as the dependent variable was the changing score (rank) of depression. Data were collected by using structured questionnaire. Data were then analyzed using wilcoxon sign rank test with level of significance of≤ 0.05.Result: The result showed, after giving spiritual guidance in accordance with Islamic religion, the score (rank) of depression for elderly to decrease than before giving spiritual guidance in accordance with Islamic religion with significant value p = 0.005.Discussion: It can be concluded that spiritual guidance in accordance with Islamic religion having strong influence for the changing score (rank) of depression of the elderly before and after it had done. It was suggested for the competence person in RT 04 Kedung Tarukan Wetan Surabaya to do this activity continuously as one of the way to prevent and to solve depression for the elderly who lived in the region of RT 04Kedung Tarukan Wetan Surabaya.